Pengaruh Penggunaan Website Bijakmemilih.Id terhadap Partisipasi Politik Generasi Z di Indonesia - Miqdad Meutuah F; Muhammad Sufyan Abdurrahman (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to analyze the effect of the use of the website bijakmemilih.id on the political participation of generation Z in Indonesia. The focus of the study is how access and use of the website can increase political participation, both in conventional and non-conventional forms. This study uses a quantitative method with a descriptive and causal approach. The independent variable in this study is the use of the website bijakmemilih.id, while the dependent variable is political participation. Data were collected using a four-choice Likert scale and analyzed using SmartPLS software. The research sample consisted of 400 respondents selected through purposive sampling techniques with the criteria of generation Z who had used the website bijakmemilih.id and were registered as permanent voters (DPT). The results showed that the use of the website bijakmemilih.id had a positive and significant effect on the political participation of generation Z, with a t-statistic value of 24,790 which is greater than 1.96 and a p-value of 0.000 which is less than 0.05. This website meets four dimensions of user needs, namely cognitive, affective, individual integrative, and tension release needs. Generation Z who actively access this website experience increased political participation, both in elections, political discussions, and involvement in communities or social movements. The conclusion is that the use of the website bijakmemilih.id has a significant impact on increasing the political participation of generation Z. Keywords: Uses and Gratifications, Political Participation, Generation Z